RENEWABLE ENERGY CONSUMPTION AND CARBON EMISSION REDUCTION IN INDONESIA’S ENERGY SECTOR - Halia Butra Aini; Endri Ahmad Dani; Fathir Moh. Abdillah; Yandri Hilman Syahrudin (Fakultas Ekonomi Universitas IBA Palembang, 2026)
Climate change has increasingly pressured countries to accelerate the transition toward sustainable and low-carbon energy systems. For developing economies such as Indonesia, renewable energy plays a strategic role in reducing carbon dioxide (CO₂) emissions while supporting long-term economic development. This study examines the effectiveness of renewable energy consumption in contributing to national emission-reduction efforts within the framework of Indonesia’s vision for Indonesia Emas 2045. Using annual data from 1990 to 2021, the analysis incorporates renewable energy consumption, industrial value added, and GDP per capita to explore their dynamic relationships with CO₂ emissions. The Autoregressive Distributed Lag (ARDL) approach is employed to assess both short-run and long-run interactions, supported by diagnostic testing, robustness checks, and impulse response analysis to ensure model stability and reliability. This research provides empirical insights into how renewable energy adoption interacts with economic and industrial structures, highlighting its role in shaping Indonesia’s low-carbon transition. The study underscores the importance of strengthening renewable energy policies, enhancing technological innovation, and aligning economic planning with environmental objectives as part of the nation’s broader strategy toward sustainable development.